2016
DOI: 10.5194/acp-16-11687-2016
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol measurements during COPE: composition, size, and sources of CCN and INPs at the interface between marine and terrestrial influences

Abstract: Abstract. Heavy rainfall from convective clouds can lead to devastating flash flooding, and observations of aerosols and clouds are required to improve cloud parameterisations used in precipitation forecasts. We present measurements of boundary layer aerosol concentration, size, and composition from a series of research flights performed over the southwest peninsula of the UK during the COnvective Precipitation Experiment (COPE) of summer 2013. We place emphasis on periods of southwesterly winds, which locally… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 101 publications
2
12
0
Order By: Relevance
“…The selected case (3 August 2013) has been previously analysed from an observational viewpoint with a focus on cloud glaciation (Taylor et al, 2016b) and aerosol concentrations, composition, and sources (Taylor et al, 2016a). Isolated shallow cumulus clouds were scattered across most of the southwestern UK in the early morning.…”
Section: Introductionmentioning
confidence: 99%
“…The selected case (3 August 2013) has been previously analysed from an observational viewpoint with a focus on cloud glaciation (Taylor et al, 2016b) and aerosol concentrations, composition, and sources (Taylor et al, 2016a). Isolated shallow cumulus clouds were scattered across most of the southwestern UK in the early morning.…”
Section: Introductionmentioning
confidence: 99%
“…Köhler theory is limited to non-volatile compounds, so it does not consider the effects of compounds of ranging volatility in the atmosphere. It has been shown that SVOCs increase the tendency for activation of CCN, which consequently affects radiative properties of clouds and hence the necessity to quantify their influence (Topping et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The former process increases the number concentration of aerosol particles while the latter increases the size, and consequently soluble mass, of existing aerosol particles. The enlarged size and altered chemical composition of the particles has a dominant effect on cloud droplet number (Dusek et al, 2006;Topping et al, 2013), and so uncertainties in the amount and composition of secondary organic aerosol mass translate into large uncertainties in cloud properties.…”
Section: Introductionmentioning
confidence: 99%
“…The CCN-based approach to calculating κ requires integrating the aerosol size distribution to find the diameter, D d , above which particles activate. The aerosol size distribution, in this case, is measured at subsaturated conditions, typically ≈ 50 % RH (Taylor et al, 2016). The number of particles that activate, however, is controlled Table 3, and the vertical error bars show the 16th and 84th quantiles of our derived values.…”
Section: Hygroscopicity Including the Effects Of Svocsmentioning
confidence: 99%
“…In field measurements, atmospheric aerosol is passed through instruments under subsaturated conditions in order to measure the size distribution and composition (Taylor et al, 2016), while the number of CCN is calculated under supersaturated conditions. Including the production, condensation, evaporation, reaction and oxidation of SVOCs directly in large-scale models is very computationally expensive and is rarely carried out, especially for more than one compound.…”
Section: Introductionmentioning
confidence: 99%